1996
DOI: 10.3109/07357909609012144
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor as Marker for Monocyte Function in Chronic Myeloid Leukemia

Abstract: The intactness of monocyte function in chronic myeloid leukemia (CML) patients as assessed by their ability to secret tumor necrosis factor was evaluated. Monocytes from CML patients continued to respond to lipopolysaccharide (LPS) stimulation even during the refractory period, suggesting different pathways for stimulation by LPS and malignant processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This is consistent with the pluripotent nature of the disorder. 29,1 Chitnis et al (1996) 30 have observed elevated TNF levels from monocytes of CML patients, mainly due to a difference in the method of culturing monocytes, since they have not taken into account the absolute number of monocytes. Since monocytes possess many regulatory functions, the observed defect in cytokine production may have important implications for the immune system in CML.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the pluripotent nature of the disorder. 29,1 Chitnis et al (1996) 30 have observed elevated TNF levels from monocytes of CML patients, mainly due to a difference in the method of culturing monocytes, since they have not taken into account the absolute number of monocytes. Since monocytes possess many regulatory functions, the observed defect in cytokine production may have important implications for the immune system in CML.…”
Section: Discussionmentioning
confidence: 99%